Impact of Digital Advertising on Out-of-Home Advertising in India - Ahmad, Alim (Digital Repository of Theses, 2025)
This study examines the relationship between digital marketing, “Out of Home” (OOH) advertising, and the application of “Generative Artificial Intelligence” (Gen AI) to improve marketing communication and coordination. The research therefore seeks to find out how each of these elements fits into a total marketing communication, specifically the Indian market. It also looks at how Gen AI can enhance the connection between digital and OOH advertising as the two forms of advertising by providing information, automating, and appealing to the individual. The study utilizes mixed method research design quantitative data collected from 213 respondents through surveys and qualitative data collected from 7 respondents through interviews. Survey data and secondary data sources are used to test the model goodness of fit and effectiveness of integrated marketing communication activities. Concerning the quantitative data, the analysis was conducted with the help of SPSS software applying tests of correlation and regression On the other hand, the qualitative data were analyzed by applying content analysis on different interviews. The outcomes of this study indicated that digital marketing and OOH advertising by themselves improve brand awareness and consumer involvement. Digital marketing is very selective flexible and quantifiable while OOH advertising offers broad reach, and tangible offline consumer encounters, especially in heavily trafficked locations. This also helped to show the symbiotic relationship which exists between digital marketing and OOH advertisements. Altogether, the mentioned tools work in synergy to give a single brand marketing message thus increasing the impact of the campaigns. Offline is supported by digital where traffic is driven to online properties while OOH advertainment aids brand recall and is a strong offline booster of online promotion. Moreover, the findings highlighted four ways that Gen AI could revolutionize marketing. Self-learning Gen AI improves a given campaign's impact through algorithms, analytics and intelligent content creation. It helps initiate targeted communication and customized media buying, thus helping brands shift from one platform to another within OOH and Digital for delivering a matched customer experience. Thus, the study reveals how the emergence of Gen AI will revolutionize how marketing is done today. It offers theoretical developments in IMC as well as managerial implications for marketers interested in the use of AI to link digital and OOH advertising. AI-integrated techniques can help brands get better marketing and more relevant communication across physical and digital domains in a constantly changing environment.